Schooling Islam : the Culture and Politics of Modern Muslim Education. - Hefner, Robert W. (Princeton University Press, 2010)
Since the Taliban seized Kabul in 1996, the public has grappled with the relationship between Islamic education and radical Islam. Media reports tend to paint madrasas--religious schools dedicated to Islamic learning--as medieval institutions opposed to all that is Western and as breeding grounds for terrorists. Others have claimed that without reforms, Islam and the West are doomed to a clash of civilizations. Robert Hefner and Muhammad Qasim Zaman bring together eleven internationally renowned scholars to examine the varieties of modern Muslim education and their implications for national an.